2014
DOI: 10.1167/14.12.10
|View full text |Cite
|
Sign up to set email alerts
|

What causes the facing-the-viewer bias in biological motion?

Abstract: Orthographically projected biological motion point-light displays are generally ambiguous with respect to their orientation in depth, yet observers consistently prefer the facing-the-viewer interpretation. There has been discussion as to whether this bias can be attributed to the social relevance of biological motion stimuli or relates to local, low-level stimulus properties. In the present study we address this question. In Experiment 1, we compared the facing-the-viewer bias produced by a series of four stic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…While bottom-up factors surely contribute (e.g., Schouten et al, 2011;Weech et al, 2014) our findings support that top-down influences like the sociobiological relevance of biological motion stimuli affect the facing-the-viewer bias. We found support that social interaction anxiety was positively associated with FTV scores, inhibitory performance was negatively associated with FTV scores, and inhibitory Fig.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…While bottom-up factors surely contribute (e.g., Schouten et al, 2011;Weech et al, 2014) our findings support that top-down influences like the sociobiological relevance of biological motion stimuli affect the facing-the-viewer bias. We found support that social interaction anxiety was positively associated with FTV scores, inhibitory performance was negatively associated with FTV scores, and inhibitory Fig.…”
Section: Resultssupporting
confidence: 68%
“…In fact, these findings shed doubt on the significance of previous findings that the gender of point-light figures affects the facing-the-viewer bias. Other factors, such as the concavity and convexity of the angles of the limbs (Weech et al, 2014) and familiarity with point-light stimuli (Troje & Davis, 2011) also surely play a role in this bias. Given the support found for both these bottom-up and top-down processes, it appears likely that the facing-the-viewer bias results from a complex interplay between several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that multisensory interaction can be modulated by an individual's cognitive traits, and conform to an unwritten social norm. This effect might arise in people with high anxiety, as mistaking an approaching person for someone who is receding might have more severe consequences than the opposite mistake (Van de Cruys et al, 2013 ; Weech et al, 2014 ). People with higher empathic concern might be more sensitive to the direction of conflicting sensory cues (as in the incongruent condition), so as to avoid a potential mistake, like those in the high-anxiety group just mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the self-serving bias, a recent study revealed that in perceiving the receding/approaching directional information for PLWs, observers with high social anxiety are less likely to report the PLW as approaching, compared to observers with low social anxiety. This bias might reflect an assumption that mistaking approach for withdrawal is worse than the reverse (Van de Cruys et al, 2013 ; Weech et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%